Content Marketing and Customer Loyalty: The Role of Engagement in Culinary SMEs in the Digital Era - Naim, Ifin; Rajuddin, Wa Ode Nursaadha (Accounting Profession Journal (APAJI), 2025)
This study investigates the effect of content marketing on customer loyalty through the mediating role of customer engagement in the context of culinary MSMEs in the digital era. Using a quantitative approach and structural equation modeling (PLS-SEM) with data from 200 respondents, the results reveal that content marketing does not directly influence customer loyalty. However, it significantly impacts customer engagement, which in turn positively affects loyalty. Furthermore, customer engagement fully mediates the relationship between content marketing and loyalty. These findings highlight the critical role of engagement in transforming content strategies into long-term customer relationships. The study offers valuable implications for MSME practitioners aiming to optimize digital content to build loyalty.